Konsumerisme dalam Perspektif Jean Baudrillard - Indra Setia Bakti; Nirzalin Nirzalin; Alwi Alwi (Sociology Department Of Syiah Kuala University, 2019)
Consumerism has revealed its form. The existence of the ideology has caused ridicule and even opposition from some groups of society, while some other groups support and make it a way of life. But times seem to influence more and more people to choose the consumerist path. Indications that support this argument can be seen from the phenomenon of society making material ownership a measure of success. This article explores consumerism in Jean Baudrillard's perspective using the literature study method. Several references such as books and journals and both written directly by Baudrillard and the works of other authors on the same theme. Baudrillard's three early works brought this study to the discussion of the concept of sign-values and simulation which had made a major contribution to the development of the sociology of consumption studies.AbstrakKonsumerisme sudah menampakkan wujudnya. Keberadaan paham ini memunculkan cemoohan bahkan penentangan dari sebagian pihak, sementara sebagian pihak yang lain justru mendukung dan menjadikannya sebagai cara hidup. Namun perjalanan waktu tampaknya menggoda semakin banyak orang untuk memilih jalan konsumeris. Indikasinya dapat dibaca dari kepemilikan komoditas tertentu sebagai ukuran kesuksesan hidup. Artikel ini mengupas tentang konsumerisme dalam perpektif Jean Baudrillard dengan menggunakan metode studi pustaka. Sejumlah referensi seperti buku dan jurnal dijadikan rujukan, baik karya yang ditulis langsung oleh Baudrillard maupun karya-karya penulis lain dalam tema yang sama. Tiga karya awal Baudrillard membawa studi ini mengerucut pada konsep nilai-tanda dan dunia simulasi yang telah memberi kontribusi besar dalam pengembangan ranah studi sosiologi konsumsi.